HIF-1 factor induced by hypoxia and oxygen sensitivity. Role of intracellular iron - Wagner Grau, Patrick (2011)
Of cellular adaptation to hypoxia and are strongly expressed under conditions of regional and systemic hypoxia. HIF-2 seems to be more related to the secretion of mature EPO interstitial fibroblasts. Upon a state of systemic hypoxia, such as anemia, induces the formation of HIF-1 and 2. Renal tubular cells express only HIF-1. The HIF2 found in glomerular cells, peritubular endothelial cells and interstitial fibroblasts. HIF-1 and HIF-2 seem to play complementary roles rather than redundant roles in vivo. Both factors have been studied in various kidney diseases: in acute kidney injury, in chronic kidney disease, in polycystic kidney disease and kidney cancer. Various chemical substances, including iron, can inhibit the HIF - prolyl - hydroxylas e (PHD) thus avoiding the degradation of HIF molecules 1 and 2 .